2021
DOI: 10.1111/pace.14254
|View full text |Cite
|
Sign up to set email alerts
|

Case series on stereotactic body radiation therapy in non‐ischemic cardiomyopathy patients with recurrent ventricular tachycardia

Abstract: Introduction The efficacy of stereotactic body radiation therapy (SBRT) as an alternative treatment for recurrent ventricular tachycardia (VT) is still unclear. This study aimed to report the outcome of SBRT in VT patients with nonischemic cardiomyopathy (NICM). Methods The determination of the target substrate for radiation was based on the combination of CMR results and electroanatomical mapping merged with the real‐time CT scan image. Radiation therapy was performed by Flattening‐filter‐free (Truebeam) syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…In 2021, several other groups presented their first experience with SBRT for VTs in small series of patients. [20][21][22][23] The results were similar to the initial studies, with relatively high mortality, reflecting the severity of heart disease in this high-risk population. Other studies showed less optimistic data.…”
Section: More Advanced Clinical Experiencesupporting
confidence: 79%
“…In 2021, several other groups presented their first experience with SBRT for VTs in small series of patients. [20][21][22][23] The results were similar to the initial studies, with relatively high mortality, reflecting the severity of heart disease in this high-risk population. Other studies showed less optimistic data.…”
Section: More Advanced Clinical Experiencesupporting
confidence: 79%
“…In 6 studies, there was a significant reduction (>80%) of VT burden at follow-up. In other studies reduction of VT burden at follow up ranges between 30 and 70% ( 9 , 10 , 16 ), or there was no reduction in one case ( 13 ).…”
Section: Resultsmentioning
confidence: 86%
“…Three retrospective case series (7)(8)(9), two retrospective (10,11), and five prospective studies (12)(13)(14)(15)(16) were included in our systematic review. The baseline characteristics of the patients included in the analysis are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Cardiac SBRT with 25 Gy in one fraction is a new and innovative treatment for patients with refractory VT (Table 2). To date, eight case reports (17-24) and 11 case series (11,12,(25)(26)(27)(28)(29)(30)(31)(32) have been published. Ninety-one patients were treated with a radiation dose of 25 Gy, and one patient was treated with 24 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial vacuolization and disruption of gap junctions on electron microscopy specimens is noted after SBRT as relatively acute effects that occur well before cellular DNA damage–related apoptosis and fibrosis begin ( 27 ). Additionally, severe architectural disruption, inflammatory cell infiltration, fibrin deposition and necrosis in myocardial tissue caused by high-dose irradiation in swine have been reported ( 22 , 30 , 31 ). Notably, irradiation with 16 Gy to the mouse heart induced mitochondrial damage and metabolic alterations of the cardiac tissue and led to structural remodeling, functional injury and fibrotic alterations ( 36 ).…”
Section: Discussionmentioning
confidence: 99%